Clinical and microbiological features of host-bacterial interplay in chronic venous ulcers versus other types of chronic skin ulcers - Mihai, Mara Mădălina; Popa, Mircea Ioan; Holban, Alina Maria; Gheorghe-Barbu, Irina; Popa, Liliana Gabriela; Chifiriuc, Mariana-Carmen; Giurcăneanu, Călin; Bleotu, Coralia; Cucu, Corina Ioana; Lazăr, Veronica (Frontiers in Microbiology, 2024)
Introduction Chronic venous ulcers of the lower limbs develop in the context of advanced venous disease and have a significant impact on the patient’s quality of life, being associated with depression and worrisome suicide rates, as well as with an economic burden caused by increased medical care costs and high epidemiological risks of healthcare associated infections and emergence of strains resistant to multiple classes of antibiotics and/ or antiseptics. Although numerous studies have investigated the composition of the chronic wounds microbiome, either by culture-dependent or independent methods, there are no data on the association between virulence and resistance profiles of strains isolated from venous ulcers and the clinical picture of this pathology. The elucidation of pathogenic mechanisms, at both phenotypic and molecular level, is crucial in the fight against these important human microbial agents, in order to develop novel biomarkers and discover new therapeutic targets. Methods In this study we aimed to characterize the phenotypic virulence profiles (including the ability to develop biofilms) of microorganisms isolated from chronic skin wounds and to correlate them with the clinical symptomatology. Considering the high incidence of Staphylococcus aureus infections in chronic ulcers, but also the ability of this species to develop multi-drug resistance, we performed an more in-depth study of the phenotypic and genotypic virulence profiles of methicillin-resistant Staphylococcus. Results The study revealed important differences regarding the clinical evolution and virulence profiles of microorganisms isolated from lower limb wounds, as well as between patients diagnosed with chronic venous ulcers and those with lesions of different etiology.